Successfully planning for SOA Part 2 - Building your SOA roadmap. - Bennett, Stephen
In this second article about service-oriented architecture (SOA), I offer a concrete plan, along with tips and insights, to help you build an effective SOA roadmap, and to help ensure the success of your SOA initiative.